High-performance anion exchange membrane alkaline seawater electrolysis. Issue 15 (8th March 2021) - Park, Yoo Sei; Lee, Jooyoung; Jang, Myeong Je; Yang, Juchan; Jeong, Jaehoon; Park, Jaeho; Kim, Yangdo; Seo, Min Ho; Chen, Zhongwei; Choi, Sung Mook
Abstract : Seawater electrolysis is a promising technology for the production of hydrogen energy and seawater desalination. To produce hydrogen energy through seawater electrolysis, highly active electrocatalysts for the oxygen evolution reaction are required. Abstract : Seawater electrolysis is a promising technology for the production of hydrogen energy and seawater desalination. To produce hydrogen energy through seawater electrolysis, highly active electrocatalysts for the oxygen evolution reaction (OER) are required. Here, we report the development of a Ni-doped FeOOH anode for high-efficiency anion exchange membrane alkaline seawater electrolysis. The Ni-doped FeOOH anode showed an overpotential of only 301 mV in half-cell tests, reaching a current density of 100 mA cm −2 in 1.0 M KOH + seawater. An anion exchange membrane electrolyzer catalyzed by Ni-doped FeOOH exhibited a current density of 729 mA cm −2 in 1.0 M KOH + seawater with an energy conversion efficiency of 76.35%. Compared to the reported AEM electrolyzer operated in 1.0 M KOH, our AEM electrolyzer catalyzed with Ni-doped FeOOH operated in 1.0 M KOH + seawater exhibited higher performance.